KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PEDAGANG DI KAWASAN WISATA PANTAI AIR MANIS KOTA PADANG 2012-2020 - Afif Ardiansyah; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2021)
This research describes the socio-economic life of the food and beverage or culinary merchant community in the tourist area of ​​Air Manis Beach, Air Manis Village, South Padang District, Padang City 2012-2020. The purpose of this research is to reveal and describe the background, socio-economic life, and the role of the government in advancing the business of the merchant community in the tourist area of ​​Air Manis Beach, Padang City. This research is a descriptive qualitative research that uses historical research methods. There are several steps taken in historical research, namely heuristics (collecting data), source criticism (criticizing data sources), interpretation (making interpretations related to historical facts) and historiography (writing history). The results of this study explain that trading business has a major influence on the socio-economic life of the merchant community in Air Manis sub-district. Many people choose to work as traders because it is difficult to find new jobs, the fishing profession is no longer reliable as their main source of income for daily life, economic factors, the benefits of large trading, and the only expertise they have. Keywords : Socio-Economic, Public, Trader